Crime and Street Children (Study on Emas Indonesia Foundation) - Supriyanti, Okias; Tarigan, Enita Apriani; Mudiyanti, Romi; Wahyuni, Ribut Tirto (Law Research Review Quarterly, 2020)
Humans are social creatures where one human needs another human being so that in their daily activities they always interact with one another. Naturally, each individual adapts to an environment that makes the individual comfortable and adapts to the environment in which he is and lives together so that there are order and order in living together, society as a container or social environment that influences the lives of the individuals in it. This research aims to analyze the phenomenon of crime among street children in the city of Semarang. This research method uses a qualitative approach, where the author sees and observes directly the various activities of street children in the city of Semarang. This research found that crime is caused by several factors such as economy, relationships, opportunities, and others. These factors that have occurred in Indonesia have shown a negative effect. A large number of people commit wrong actions with the sole purpose of wanting to make ends meet. Street children choose the environment on the streets sometimes not only because of economic hardship but also because they enjoy the environmental conditions on the streets. Street children do not always have a place to live, children who feel stressed by the condition of their family and home environment, sometimes feel more comfortable choosing the streets as their living environment.